2015
DOI: 10.1111/obes.12111
|View full text |Cite
|
Sign up to set email alerts
|

Envy and Habits: Panel Data Estimates of Interdependent Preferences

Abstract: We estimate the importance of preference interdependence from consumption choices. Our strategy follows the literature that tests the constraints imposed by optimality in the evolution of individual consumption. We derive an Euler equation from a preference specification that allows for nonseparabilities across households and across time. The introduction of habits and envy places additional restrictions on the evolution of the optimal consumption path. We use a unique data set that follows a sample of 3,200 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 94 publications
2
23
1
Order By: Relevance
“…The R 2 of all estimations is around 0.10, indicating that a non-negligible fraction of the variance of observed consumption growth in our sample can be explained by the included controls. Unfortunately, we cannot compare this figure to other studies estimating log-linearised Euler equations, such as Dynan (2000) or Alvarez-Cuadrado et al (2012), since these studies do not report the R 2 .…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The R 2 of all estimations is around 0.10, indicating that a non-negligible fraction of the variance of observed consumption growth in our sample can be explained by the included controls. Unfortunately, we cannot compare this figure to other studies estimating log-linearised Euler equations, such as Dynan (2000) or Alvarez-Cuadrado et al (2012), since these studies do not report the R 2 .…”
Section: Resultsmentioning
confidence: 54%
“…The first one postulates that individuals compare themselves to other individuals living in the same geographical area (Blanchflower and Oswald, 2004;Luttmer, 2005;Ravina, 2007;Alvarez-Cuadrado et al, 2012). The second approach assumes that individuals compare themselves primarily to other individuals sharing certain demographic characteristics such as age, gender, education or profession (Alessie and Kapteyn, 1991;Maurer and Meier, 2008;Lewbel et al, 2013).…”
Section: Construction Of the Independent Variables And Study Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The empirical evidence in favor of interdependent consumption dates back to Pollak and Wales (1978) and since then has been growing continuously until the recent works of Alvarez-Cuadrado et al (2016) andDe Giorgi et al (2017). Scholars have shown that evidence of interdependent choices can be found in aggregate consumption expenditures, many consumption categories, investment strategies and is robust across different countries.…”
Section: Db(t) = R(t)b(t)dtmentioning
confidence: 99%